Serum Alkaline Phosphatase Negatively Affects Endothelium-Dependent Vasodilation in Naïve Hypertensive Patients. Issue 4 (October 2015) - Perticone, Francesco; Perticone, Maria; Maio, Raffaele; Sciacqua, Angela; Andreucci, Michele; Tripepi, Giovanni; Corrao, Salvatore; Mallamaci, Francesca; Sesti, Giorgio; Zoccali, Carmine
<x xml:space="preserve">Abstract</x> Tissue nonspecific alkaline phosphatase, promoting arterial calcification in experimental models, is a powerful predictor of total and cardiovascular mortality in general population and in patients with renal or cardiovascular diseases. For this study, to evaluate a possible correlation between serum alkaline phosphatase levels and endothelial function, assessed by strain gauge plethysmography, we enrolled 500 naïve hypertensives divided into increasing tertiles of alkaline phosphatase. The maximal response to acetylcholine was inversely related to alkaline phosphatase (r=−0.55; P<0.001), and this association was independent (r=−0.61; P<0.001) of demographic and classical risk factors, body mass index, estimated glomerular filtration rate, serum phosphorus and calcium, C-reactive protein, and albuminuria. At multiple logistic regression analysis, the risk of endothelial dysfunction was ≈3-fold higher in patients in the third tertile than that of patients in the first tertile. We also tested the combined role of alkaline phosphatase and serum phosphorus on endothelial function. The steepness of the alkaline phosphatase/vasodilating response to acetylcholine relationship was substantially attenuated (P<0.001) in patients with serum phosphorus above the median value when compared with patients with serum phosphorus below the median (−5.0% versus −10.2% per alkaline phosphatase unit, respectively), and this interaction remained highly significant (P<0.001) after adjustment of all the previously mentioned risk factors. Our data support a strong and significant inverse relationship between alkaline phosphatase and endothelium-dependent vasodilation, which was attenuated by relatively higher serum phosphorus levels.